Linking entrepreneurial spirit and entrepreneurial environment perception to entrepreneurial intention: Moderation by entrepreneurial role models - Biyan Xiao; Xiaoqing Wang; Qianhong Liu; Peng Zhang (PLoS ONE, 2026)
Entrepreneurial intention is widely recognized as a key precursor of entrepreneurial behaviour, yet existing research has more often examined personal entrepreneurial characteristics and perceived environmental support separately, with less attention to how they jointly shape intention and how entrepreneurial role models may condition these relationships. Guided primarily by social cognitive theory and complemented by the Theory of Planned Behavior, this study develops an integrated model to examine how entrepreneurial spirit, reflected in innovativeness and proactiveness, and entrepreneurial environment perception, reflected in perceived access to finance, perceived entrepreneurial education, and perceived policy support, are related to college students’ entrepreneurial intention, and whether these relationships are strengthened by entrepreneurial role models. Using survey data from 1,389 students in higher education institutions in Shandong Province, China, the hypotheses were tested through confirmatory factor analysis, structural equation modelling, and hierarchical regression. The results show that both entrepreneurial spirit and entrepreneurial environment perception are positively associated with entrepreneurial intention. In addition, entrepreneurial role models significantly strengthen the relationships between entrepreneurial spirit and entrepreneurial intention, and between entrepreneurial environment perception and entrepreneurial intention. These findings contribute to entrepreneurship intention research by showing that entrepreneurial intention is shaped not only by person-related dispositions and perceived support conditions, but also by role-model-based social learning that makes entrepreneurial pathways more credible and attainable for students.